Desempeño en el área de créditos sobre la cartera morosa en la CMAC de Piura Agencia Huamachuco Periodo 2019-2021 - Mujica Saman, Kattia Marisella (2021)
The following labor sufficiency report aimed to determine the performance in the credit area on the delinquent portfolio in CMAC de Piura agency Huamachuco 2019-2021; the problems that arose during my experience are: The main problem detected is that the delinquent portfolio was increasing, since in 2019 it was 7.52%, this is due to the fact that the assigned portfolio was not monitored and stay in touch with my clients who are late. As a result, the portfolio at risk for the year 2019 was S/ 112,871.42, for the year 2020 it was S/ 192,385.02 and for the year 2021 it was S/ 101,892.47. The doubtful portfolio for the year 2019 was S/ 75,200.80, for the year 2020 it was S/ 192,571.49 and for the year 2021 it was S/ 88,658.36. The portfolio in loss for the year 2019 was S/ 85,739.39, for the year 2020 it was S/ 166,276.86 and for the year 2021 it was S/ 84,667.73. Concluding that with the implementation of improvements, the delinquency rate went from 7.52% in 2019 to 6.17% in 2021, generating a reduction of 1.36%.